Perkembangan Putusan Mahkamah Konstitusi dalam Menangani Perkara Perselisihan Hasil Pemilihan Umum Presiden - Ning Ayunda Chofifi; Eny Kusdarini (Fakultas Hukum Universitas Islam Indonesia, 2024)
This paper analyzes the development of the Constitutional Court Decision in addressing the Dispute on the Presidential and Vice Presidential Election Results (PHPU) and the impact of the said decision on the legitimacy of the election results and the political stability in Indonesia. This is a normative legal research with a library study approach and literature study. The results of the study conclude that, first, Constitutional Court Decisions which address the Disputes on the Presidential and Vice Presidential Election Results since 2004, 2009, 2014, 2019 and 2024 have repetitively rejected the application thus the PHPU lawsuits have never been granted. However, in the 2024 trial, three justices posed their dissenting opinion. The dissenting opinion in the 2024 trial was the first to occur in the history of the Presidential Election disputes in Indonesia. The dissenting opinion presented by the three Constitutional Court justices is evidence that there remain critical voices that are committed to the principles of justice and democracy. In general, the development of Constitutional Court decisions display significant evolution in terms of procedural, substantive, and interpretive aspects with the increasing use of stricter and more transparent legal principles, as well as efforts to ensure the fairness and validity of the election process. Second, the impact of Constitutional Court decisions on the legitimacy of election results and the political stability in Indonesia, namely maintaining public trust in the election process, can contribute to a peaceful transition of power, and strengthen the democratic system. Public trust in the Constitutional Court is a fundamental pillar in maintaining constitutional justice and the supremacy of law in Indonesia.Keywords: Constitutional Court Decision, Development, General Election Results Dispute, Presidential Election. AbstrakTulisan ini menganalisis perkembangan Putusan Mahkamah Konstitusi dalam menangani Perkara Perselisihan Hasil Pemilihan Umum (PHPU) Presiden dan Wakil Presiden serta dampak putusan terhadap legitimasi hasil pemilihan umum dan stabilitas politik di Indonesia. Penelitian ini merupakan penelitian yuridis normatif dengan pendekatan studi kepustakaan dan studi literatur. Hasil penelitian menyimpulkan, pertama, Putusan Mahkamah Konstitusi dalam menangani PHPU Presiden dan wakil Presiden dari sejak tahun 2004, 2009, 2014, 2019 dan 2024 menolak permohonan pemohon dan tidak pernah terjadi pengabulan gugatan PHPU. Namun, pada sidang 2024 tiga hakim memiliki pendapat berbeda (dissenting opinion). Dissenting opinion pada sidang 2024 merupakan yang pertama terjadi dalam sejarah sengketa Pilpres di Indonesia. Dissenting opinion yang disajikan oleh tiga hakim MK menjadi bukti bahwa masih ada suara-suara kritis yang berkomitmen pada prinsip keadilan dan demokrasi. Secara keseluruhan, perkembangan putusan Mahkamah Konstitusi menunjukkan evolusi yang signifikan dari aspek prosedural, substansial, dan interpretatif dengan peningkatan penggunaan prinsip-prinsip hukum yang lebih ketat dan transparan, serta upaya untuk memastikan keadilan dan keabsahan proses pemilihan. Kedua, dampak putusan Mahkamah Konstitusi terhadap legitimasi hasil pemilihan umum dan stabilitas politik di Indonesia yakni menjaga kepercayaan masyarakat terhadap proses Pemilu, dapat berkontribusi pada transisi kekuasaan secara damai, dan memperkuat sistem demokrasi. Kepercayaan masyarakat terhadap Mahkamah Konstitusi merupakan pilar fundamental dalam terpeliharanya keadilan konstitusi dan supremasi hukum di Indonesia.Kata Kunci: Pemilihan Presiden, Perkembangan, Perselisihan Hasil Pemilihan Umum, Putusan Mahkamah Konstitusi.